2022
DOI: 10.2147/ijgm.s384233
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Profile and Risk Factors of Nosocomial Infection in Ayder Pediatric Intensive Care Unit, Tigray, Ethiopia

Abstract: Background Hospital-acquired infection (HAI) is a significant cause of increased morbidity and mortality amongst hospitalized patients and represents a considerable health and economic burden worldwide. However, evidence about HAI in pediatric ICU is limited. Objective To identify the prevalence of hospital-acquired infection (HAI), clinical profile, and its risk factors for nosocomial infection in patients admitted to the pediatric intensive care unit (PICU). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The current study also demonstrated that paediatric patients who received antibiotics at admission had 4.76 times higher odds of developing nosocomial infections compared to those who did not receive antibiotics at admission. This finding is similar to the study conducted at Ayder Hospital (26). One potential explanation for this association could be overuse or inappropriate use of antibiotics, which can lead to antibiotic resistance and subsequent infections.…”
Section: Factors Associated With Nosocomial Infection Among Paediatri...supporting
confidence: 88%
See 2 more Smart Citations
“…The current study also demonstrated that paediatric patients who received antibiotics at admission had 4.76 times higher odds of developing nosocomial infections compared to those who did not receive antibiotics at admission. This finding is similar to the study conducted at Ayder Hospital (26). One potential explanation for this association could be overuse or inappropriate use of antibiotics, which can lead to antibiotic resistance and subsequent infections.…”
Section: Factors Associated With Nosocomial Infection Among Paediatri...supporting
confidence: 88%
“…The odds of developing nosocomial infections among paediatric patients who were malnourished were 2.01 times higher compared to those who were well-nourished [AOR=2.01; 95%CI(1.18, 5). (25) and Ayder Hospital (20.2%) (26). However, it is higher when compared to previous studies conducted in Ecuador (13.5%) (36), Switzerland (6.7%) (28), the Philippines (11.37%) (37), the South of Iran (14.57%) (38), and Kenya (2.62%) (39).…”
Section: Factors Associated With Nosocomial Infection Among Paediatri...mentioning
confidence: 69%
See 1 more Smart Citation
“…The mean duration of mechanical ventilation in those patients with and without NI was 1.65 days and 13.96 days, respectively. Patients who started antibiotics at admission and patients who were on nasogastric tube feeding were also statistically significant risk factors for developing NI [21] . As a conclusion, the review identified a number of essential details about the rate of HAIs in different parts of the world.…”
mentioning
confidence: 99%